«Євхаристиріон, або Вдячність...» Софронія Почаського у віршознавчому зрізі - Гуцуляк, Микола; Gutsuliak, Mykola (Східноєвропейський національний університет імені Лесі Українки, 2015)
Здійснено віршознавчий аналіз пам’ятки початку 30-х років XVII ст. – панегіричної поеми «Ευχαριστηριόν, албо Вдячность...», редактором і вірогідним автором якої був Софроній Почаський. Увагу зосереджено на ритміці силабічних версів, їх наголошуваності та особливостях цезури й рими.The article has conducted the versificational analysis of the mid 17th century panegyric poem «Ευχαριστηριόν, or gratitude...» which was edited and probably written by Kievan professor of rhetoric Sofronij Pochasky. During the analysis it should be solved a number of problems, namely: classification and study of the 13-syllable verse rhythmic forms; setting the proportion of «pure» and «impure» forms; determination the percentage of tonization in hemistichs and syllabic verse in general; determination the percentage of accentuation of each position in the 13-syllable verse-line; study the features of caesura and rhyme. The statistical calculations are the main instrument for our analysis. The publication of the work performed by F. Titov in 1924 was elected as the source of the text. In this publication the author’s spelling and stresses was saved, which is important to minimize the subjective factor in the preparation of rhythmic schemes. The study revealed that Sofronij Pochasky’s panegyric was monometric poem, since it was composed almost entirely of thirteen-syllable verses, which are combined into couplets by an adjacent, feminine, mostly exact rhyme.
Sofronij Pochasky’s «Evharistirion, or Gratitude...» in Versificational Aspect
Keywords: силабіка; склад; наголос; цезура; ритм; ритмічна форма; рима; syllabics; syllable; stress; caesura; rhythm; rhythmic form; rhyme